2014
DOI: 10.1002/jor.22767
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐induced apoptosis and matrix loss of chondrocytes is inhibited by eicosapentaenoic acid

Abstract: Eicosapentaenoic acid (EPA) is an antioxidant and n-3 polyunsaturated fatty acid that reduces the production of inflammatory cytokines. We evaluated the role of EPA in chondrocyte apoptosis and degeneration. Normal human chondrocytes were treated with EPA and sodium nitroprusside (SNP). Expression of metalloproteinases (MMPs) was detected by real-time polymerase chain reaction (PCR) and that of apoptosis-related proteins was detected by western blotting. Chondrocyte apoptosis was detected by flow cytometry. C5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 19 publications
1
40
0
1
Order By: Relevance
“…This DNA degradation was profoundly inhibited in the presence of NAC, a ROS scavenger, suggesting again the requirement of ROS in SNP-induced cell death [219]. Accordingly, intra-articular injection of antioxidants, such as N -acetylcysteine (NAC) or eicosapentaenoic acid (EPA), prevented cartilage destruction and apoptosis, in vivo, in a rat model of experimentally-induced OA [228] or in a DMM mouse model of OA [229], respectively. SNP-induced NO could induce cell death via the downstream production of ROS, NAC, neutralizing NO-induced ROS in rabbit cultured chondrocytes.…”
Section: Cell Death Regulators In Chondrocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…This DNA degradation was profoundly inhibited in the presence of NAC, a ROS scavenger, suggesting again the requirement of ROS in SNP-induced cell death [219]. Accordingly, intra-articular injection of antioxidants, such as N -acetylcysteine (NAC) or eicosapentaenoic acid (EPA), prevented cartilage destruction and apoptosis, in vivo, in a rat model of experimentally-induced OA [228] or in a DMM mouse model of OA [229], respectively. SNP-induced NO could induce cell death via the downstream production of ROS, NAC, neutralizing NO-induced ROS in rabbit cultured chondrocytes.…”
Section: Cell Death Regulators In Chondrocytesmentioning
confidence: 99%
“…The apoptosis-preventing activity of NAC was mediated by glutathione, as a glutathione synthetase inhibitor abrogated NAC protective effects [228]. In vitro, EPA and NAC were able to reduce SNP-induced caspase-3 cleavage, as well as p53 [228,229] and p38 phosphorylation [229]. Other studies have supported that NO was not able to induce apoptosis, as the production of high levels of endogenous NO (by adenoviral-mediated over-expression of the iNOS gene) in adenoviral transfected chondrocytes failed to induce cell death [230].…”
Section: Cell Death Regulators In Chondrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of MAPKs regulates downstream redox-sensitive transcription factors, such as p53 and Nrf2, to control the expression of downstream pro-apoptotic and anti-apoptotic genes [30, 31]. Nrf2 regulates the transcription of a number of antioxidant enzymes by binding to the antioxidant response element (ARE) in the promoter regions of genes such as glutathione synthesis enzymes and thioredoxin-1, among others, and regulates the expression of the anti-apoptotic gene Bcl-2 .…”
Section: Discussionmentioning
confidence: 99%
“…The level of chondrocyte degeneration is correlated with the pathogenesis of osteoarthritis (OA), the most common chronic joint disease [35][36][37]. At the molecular level, Shuhei Sakata et al evaluated the effects of EPA on OA and found that EPA dramatically inhibited sodium nitroprusside (SNP)-induced chondrocyte apoptosis by suppressing phosphorylation of p38 mitogen-activated protein kinase (MAPK) and p53, caspase 3 and poly(ADP-ribose) polymerase cleavage, and expression of matrix metalloproteinases (MMPS) (Figure 3) [38].…”
Section: Cardioprotective Effectmentioning
confidence: 99%